Foreign Trade-Foreign Exchange Nexus in Nigeria: A Vector Error Correction Modelling Approach - Olushina Olawale Awe; Damola M. Akinlana; Sherifat Omolola Adesunkanmi (Binus Business Review, 2016)
This study investigates trade foreign exchange nexus in Nigeria. This study is also done with a view to detecting the kind of relationship that exists between the two and also to investigate their co-integration. Annual time series data for the period 1996 – 2010 was used for the study. The Vector Correction Model (VECM) approach was employed to determine both the short and long run relationships. Results showed that the series becomes stationary after second difference. The co – integration test reveals five co – integrating vectors in the model, implying that the variables have the same stochastic drift. The study concludes that a long-term relationship exists between foreign trade and exchange rates implying that foreign trade flows have a strong link with exchange rates in Nigeria.